2018
DOI: 10.1007/s00253-018-9197-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the mitochondrial alternative oxidase gene (aox1) from Aspergillus niger CGMCC 10142 and its effects on citric acid production

Abstract: In this work, we constructed the aox1 disruption strains 3-4 and 4-10, as well as the aox1 overexpression strains 72 and 102 in Aspergillus niger. The energy metabolism, EMP, TCA pathways, and flux were investigated for the citric acid (CA) overproduction via the aox1 overexpression among them. As expected, the overexpression of the aox1 gene enabled a higher growth rate than that of the rate of its parent strain in medium with respiratory chain inhibitors. In liquefied corn starch medium supplemented with 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…Moreover, antimycin A compound used in the study is stated as an inhibitor of AOX protein, which is in contradiction with the effect sought by the overexpression of aox1. In the absence of contradicting our study, Hou et al (2018) confirm the hypothesis that AOX may contribute to clearing ROS species and improving cell survival. www.nature.com/scientificreports/…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, antimycin A compound used in the study is stated as an inhibitor of AOX protein, which is in contradiction with the effect sought by the overexpression of aox1. In the absence of contradicting our study, Hou et al (2018) confirm the hypothesis that AOX may contribute to clearing ROS species and improving cell survival. www.nature.com/scientificreports/…”
Section: Discussionsupporting
confidence: 88%
“…The proposed mechanism is in good agreement with the work of Kavšček et al, and Sabra et al, showing that the fine modulation of oxygen consumption enzymes in Y. lipolytica favors citrate overflow metabolism. A recent study of citrate production in Aspergillus niger by disruption or overexpression of aox1 gene, in addition to antimycin A during cell growth, showed an improved citrate production in overexpressed aox1 strains compared to the parental strain 55 . Up to 169.1 g/L citrate is reported for one of the overexpressed strains against 158.9 g/L for the parental stain.…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al. (2018) modified A. niger strain CGMCC10142 by deleting and overexpressing mitochondrial AOX gene aox 1 and uncovered that the overexpression of aox 1 gene improve CA production, and cyanide‐resistant respiration (CRR) respiration was detected in mycelia of A. niger under CA production conditions. The presence of AOX thus alleviates the repression of PFK due to excess ATP and relieving the damage caused by ROS as well (Campos et al., 2015).…”
Section: Metabolic Engineering Of Ca Productionmentioning
confidence: 99%
“…These findings would imply that the operation of the alternative oxidase is essential for citric acid accumulation. However, Hou et al ( 2018 ) found that strains in which one of the alternative oxidase genes ( aoxA ) had been knocked out displayed only a 25% reduced citric acid yield in a high producing strain of A . niger .…”
Section: Nadh Reoxidation and Production Of Atpmentioning
confidence: 99%